PENERAPAN METODE CERTAINTY FACTOR PADA SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT VERTIGO - Dedi Setiadi; Asep Syaputra; Tri Susanti (LPPM UNIVERSITAS BINA INSAN, 2021)
The use of computers has touched various areas of life, thus encouraging experts to develop the use of computers in order to facilitate human work, one of which is in the health sector, namely the existence of an expert system used to diagnose vertigo. using the certainty factor method. Vertigo is a spinning headache sensation that is felt inside and outside the head. The certainty factor method will be applied in building this expert system, because this method can determine the value of the confidence and non-confidence weights. The results of this study are in the form of an expert system to facilitate puskesmas employees in registering and diagnosing. Testing this system using blackbox testing with a score of 3.5 from expert review and 3.5 from beta implementation with a valid category so that the resulting system can be used to diagnose vertigo at Sidorejo Health Center